A non-intrusive image analysis technique for measurement of heterogeneity in grass species around tree vicinity in a green infrastructure. (January 2018) - Gadi, Vinay Kumar; Garg, Ankit; Prakash, Shiv; Wei, Lili; Andriyas, Sanyogita
Highlights: Visual analysis as new measurement approach for studying tree-grass interaction. Vegetation density in tree vicinity is found to be more non-uniform than shoot growth. Vegetation growth is more heterogeneous during transition from dry to wet period. Grass growth is much higher away from tree stem than near tree stem. Abstract: Spatial heterogeneity of vegetation growth is important for maintenance of urban green space. It also governs the differential settlement of foundation of buildings and performance of biofiltration units. The objective of this study is to analyse the heterogeneity in vegetation density and shoot growth of a grass around a tree vicinity. A novel non-intrusive image analysis approach was designed and developed for quantifying heterogeneity in vegetation growth. A commercially available unmanned air vehicle (UAV; PHANTOM 3 STANDARD) was utilized to capture images. Vegetation density from these captured images were quantified using a public domain image processing program ImageJ. Atmospheric parameters were monitored by micro-climate monitoring system for interpreting vegetation growth. It is found that, at a given radial distance from stem of tree, vegetation density range is found more heterogenous than shoot growth. The basic assumption of symmetricity around tree vicinity as adopted in previous models for root water uptake is found to be not true. Variation of rainfall is one of the main reason causing heterogeneity in grass growth around tree vicinity. Heterogeneity in vegetation growth more prominent near the tree vicinity than away from it. An increase in vegetation density is found within 2 m radial distance in both sides of tree stem due to presence of shredded leaves from tree during winter.